Influence of amount of red worm (Eisenia foetida) on the organic matter degradation during vermicomposting of cattle manure (Bangladesh Journal of Animal Science, 2020)
This study aimed to understand the degradation pattern of organic substances through different amount of red worms during vermicomposting of cattle manure. For this purpose, an experiment was conducted with three treatments e.g., T1 (vermicomposting of 25 kg cowdung using 50 g of red worms), T2 (vermicomposting of 25 kg cowdung using 100 g of red worms) and T3 (vermicomposting of 25 kg cowdung using 150 g of red worms) with 3 replications. Parameters studied were dry matter (DM), organic matter (OM), ash, organic carbon (OC), total nitrogen (TN), crude fiber (CF), carbon nitrogen ratio (C/N) and pH at different days of intervals. Results showed that the amount of red worms has a significant influence on the quality of the final vermicompost. The highest DM content was observed in T3 and the lowest DM content was observed in T1 after 45 days of composting. There were significant (p